Athens II: Athens in late antiquity - Tanaseanu-Döbler, Ilinca; Tanaseanu-Döbler, Ilinca; Alvensleben, Leonie von; Alvensleben, Leonie von (Civitatum orbis mediterranei studia, 2020)
Cover -- Title -- Foreword -- Table of Contents -- Ilinca Tanaseanu- Döbler (with the collaboration of Leonie von Alvensleben) - Athens in Late Antiquity - Learning and Paganism -- I. Roman Athens: Real and Imagined -- Christoph Auffarth - Athen - die heilige Stadt: Erbe, Umdeutung, Palimpsest der Sakrallandschaft -- Heinz- Günther Nesselrath - Philostratus' Apollonius in Imperial Athens: Old Values and Modern Decadence -- II. Late Antique Athens: Archaeological Aspects -- Arja Karivieri - The Archaeology of Athens in Late Antiquity -- Tasos Tanoulas - The Acropolis in Late Antiquity -- Balbina Bäbler - From Asclepius to the 'Saints without Silver': The Transformation of a Sanctuary in Late Antique Athens -- Georgios Deligiannakis - From Paganism to Christianity in Late Antique Athens: A Re-Evaluation -- III. Symbolic Constructions of Athens: Athens as an Epitome of Culture -- Jan R. Stenger - Learning City: The Athenian Experience in Late Antiquity -- Michael Schramm - Julian, Athens, and the Athenians -- Jochen Schultheiß - Athens as a Cultural Symbol in Christian Authors -- IV. Schools and their Social Context -- Stefanie Holder - The Inner Structure of Schools in 3rd and 4th century Athens -- Edward Watts - Athens, Educational Reform, and the Future of Philosophy -- Anthony Kaldellis - The Politics of Classical Genealogies in the Late Antique Roman East -- V. Athenian Neoplatonism: Philosophy and Religion -- Irmgard Männlein- Robert - Vom Piräus zur Akropolis, oder: Das spätantike Athen der Hellenen. Zur Bedeutung von Wegen und Räumen in der Vita Procli des Marinos -- Sarah Klitenic Wear - Syrianus and the Shape of Platonist Philosophy in Late Antique Athens: Evidence from the Parmenides Commentary Tradition -- Ilinca Tanaseanu- Döbler - Patron Goddess of Athens - Patron Goddess of Philosophy? Athena in Proclus and the Neoplatonic Tradition.